Is energy efficiency reflected in residential property prices in Portugal?: an investigation based on hedonic house price functions and quantile regression analysis - Evangelista, Rui Alexandre Alves (2019)
This thesis investigates the degree to which energy efficiency, as it is assessed by Energy Performance Certificates (EPCs), is reflected in residential property prices in Portugal. Its results are based on the analysis of a comprehensive dataset containing information of around 256 thousand residential property sales carried out from 2009 to 2013, a period largely characterized by depressed market conditions. This is the first large-scale study for a southern European country in this area of research. For the first time in this context, the impact of energy efficiency is analyzed along the distribution of residential property prices, using the unconditional quantile regression framework. The findings disclose a 13% sales premium for most energy efficient apartments (i.e. those bearing an A or B EPC rate) and a 5 to 6% market price premium for houses. However, quantile regression results show that the value attached to energy efficiency is not always positive across the distribution of prices. In particular, houses located at or below the 0.2th price quantile display clear energy efficiency price discounts. The use of different energy efficiency scales and cross-country comparisons support the view that energy efficiency price premiums are higher in the Portuguese residential market than in northern European markets. These results contribute to a more comprehensive understanding of the impact of energy efficiency on the real estate market and provide important messages to all political decision-makers interested in improving energy efficiency standards in Portugal; É A EFICIÊNCIA ENERGÉTICA REFLETIDA NOS PREÇOS DOS IMÓVEIS RESIDENCIAIS EM PORTUGAL? Uma investigação baseada em funções de preços hedónicas e na análise de regressão por quantis Resumo: Esta tese investiga em que medida a eficiência energética, tal como é avaliada pelos Certificados de Desempenho Energético (CDE), é refletida nos preços dos imóveis residenciais em Portugal. Os resultados obtidos baseiam-se na análise de um conjunto exaustivo de dados com informação sobre cerca de 256 mil vendas de imóveis realizadas entre 2009 e 2013, um período predominantemente caracterizado pela recessão. Este é o primeiro estudo de larga escala realizado para um país do sul da Europa nesta área de investigação. Pela primeira vez neste contexto, o impacto da eficiência energética é analisado ao longo da distribuição dos preços das habitações através do método da regressão por quantis incondicionais. Os resultados revelam um prémio na venda de 13% para os apartamentos mais eficientes em termos energéticos (i.e., aqueles com CDE A ou B), e de 5 a 6% para as moradias. No entanto, a análise de regressão por quantis mostra que o valor associado à eficiência energética nem sempre é positivo ao longo da distribuição dos preços. Em particular, as moradias situadas abaixo do vigésimo percentil mostram claros descontos associados à maior eficiência energética. A utilização de diferentes escalas energéticas e a comparações entre países apoia a ideia de que os prémios associados à eficiência energética são maiores no mercado português do que em mercados do norte da Europa. Estes resultados contribuem para um conhecimento mais amplo do impacto da eficiência energética no mercado imobiliário e fornecem importantes mensagens a todos os decisores políticos interessados em melhorar os padrões de eficiência energética em Portugal.